The delay of contrast arrival in magnetic resonance first-pass perfusion imaging: a novel non-invasive parameter detecting collateral-dependent myocardium. Issue 7 (7th March 2007) - Muehling, O M; Huber, A; Cyran, C; Schoenberg, S O; Reiser, M; Steinbeck, G; Nabauer, M; Jerosch-Herold, M
Abstract : Aim: To establish the regional delay of contrast arrival in magnetic resonance perfusion imaging (MRPI) for the detection of collateral-dependent myocardium in patients with coronary artery disease. Design and setting: Observational study, case series; single centre, university hospital. Patients: 30 patients with coronary artery disease and collateral-dependent myocardium and 17 healthy volunteers. Methods: Resting and hyperaemic (adenosine) MRPI was used to determine the delay time (Δtd ) of contrast arrival between the left ventricle and collateral-dependent or antegradely perfused myocardium, and myocardial perfusion (MP, ml/min/g). Results: In healthy volunteers, mean (SD) Δtd at rest and during hyperaemia were 0.8 (0.4) and 0.3 (0.3) s, and MP was 1.14 (0.21) and 4.23 (1.12) ml/min/g. In patients Δtd in antegradely perfused vs collateral-dependent myocardium was 0.9 (0.7) vs 1.7 (1.0) s at rest (p<0.001), and 0.4 (0.3) vs 1.1 (0.6) s (p<0.001) during hyperaemia. MP was 1.12 (0.11) and 0.98 (0.28) ml/min/g (p = NS) at rest and 2.46 (0.85) vs 1.86 (0.91) ml/min/g (p<0.01) during hyperaemia. Receiver operating characteristics analysis showed the best sensitivity and specificity of 90% and 83% for hyperaemic Δtd of >0.6 s (area under the curve (AUC) = 0.89) to detect collateral-dependent myocardium, while resting Δtd (AUC = 0.77) and perfusion (AUC = 0.69 at rest or 0.70 during hyperaemia) were less accurate. Conclusions: MRPI-derived hyperaemic delay of contrast arrival detects collateral-dependent myocardium with high sensitivity and specificity. Perfusion was less sensitive, emphasising the clinical role of Δtd in non-invasive detection of collateral-dependent myocardium.